The Effect of The Marketing Mix on Coffee Sales Performance: Empirical Evidence From an Indonesian SME - Afiati, Lely (Global Sustainability Research Institute, 2026)
This study aims to examine the influence of the marketing mix, consisting of product, price, place, and promotion, on the sales performance of Nuansa Gembira Coffee in Indonesia. The research adopts a descriptive approach by integrating quantitative and qualitative methods to provide a comprehensive understanding of consumer behavior and marketing effectiveness. Data were collected from 300 respondents who had purchased and consumed Nuansa Gembira Coffee, ensuring that the sample represented actual customers with direct product experience. The findings reveal that the marketing mix variables simultaneously have a positive and significant effect on sales, indicating that an integrated marketing strategy plays an important role in improving sales performance. When analyzed individually, the place variable emerges as the most influential factor, highlighting the importance of distribution channels, product availability, and ease of access in driving consumer purchasing decisions. In contrast, product, price, and promotion do not demonstrate a significant individual influence on sales. These results suggest that while product quality, pricing strategy, and promotional activities remain important, their effectiveness may depend on how well the product is distributed and accessed by consumers. Based on these findings, this study recommends that Nuansa Gembira Coffee strengthen its distribution network, ensure consistent product availability, maintain the use of high-quality coffee beans as the main raw material, expand flavor variants, and improve packaging design. These strategies are expected to enhance competitiveness and support sustainable sales growth in the Indonesian coffee market.